Triple Therapy More Cost-effective than Biologic First in Patients Who Fail MTX - Nierengarten, Mary Beth (MD Conference Express, 2014)
For patients with rheumatoid arthritis (RA) who fail methotrexate (MTX), using a biologic instead of triple therapy first is not a cost-effective use of health care resources due to the large additional costs for very small benefits. This article presents the results of a randomized noninferiority trial that compared the cost-effectiveness of treating patients who fail MTX with a biologic first or adding triple therapy followed by a biologic.